Strategi Guru Pendidikan Agama Islam Mengembangkan Kompetensi Sikap Spiritual Dan Sikap Sosial Siswa - Wati Veranda; Subhan; Muh.Yamin (Indonesian Journal of Islamic Educational Review, 2024)
This study discusses the Strategy of Islamic Religious Education Teachers in developing Spiritual and social attitudes competencies of students at SDN 381 Kanan Kab. Luwu. This study aims: To know the condition of the spiritual and social attitudes of students in Elementary School 381 Kanan, to describe the strategy of Islamic religious education teachers in developing the competence of spiritual attitudes and social attitudes of students at SDN 381 Kanan Kab. Luwu and to describe the obstacles faced by Islamic religious education teachers in developing the competence of spiritual attitudes and social attitudes of students at SDN 381 Kanan Kab. Luwu. This research uses a qualitative approach with field researh methods. Data collection techniques use observation, interview and documentation methods. This study shows that: the problems that exist in students' attitudes are that there is still bullying between students in the class, not being serious while attending lessons, not respecting teachers and throwing rubbish carelessly; and then the strategy of Islamic religious education teachers in developing the competence of spiritual attitudes and social attitudes of students at SDN 381 Kanan Kab. Luwu namely showing a good example, providing direction/guidance providing, providing encouragement /motivation, and giving punishment to student who violate.